Addressing procedural challenges of ethical review system: Towards a better ethical quality of clinical trials review in Malaysia - See, Hooi Yan; Mohamed, Mohd Salim; Mohd Noor, Siti Nurani; Low, Wah Yun (Taylor & Francis, 2019)
The review of clinical trials with human participants in Malaysia is governed by a decentralized control system. The clinical trial protocols are reviewed by 13 registered research ethics committees (RECs) in Malaysia. A governmental body, the National Pharmaceutical Control Bureau, is responsible for the inspection and oversight of these registered RECs to ensure that they comply with the regulatory requirements. However, this study highlights that each REC in Malaysia has a different standard operating procedure and ethical review process. Other procedural challenges identified include inadequate membership, poor mechanism for research monitoring after ethical approval, and insufficient resources. Establishments of a national standard of REC and a central ethics committee are suggested to ensure procedural compliance in the oversight of clinical trials in Malaysia. While there is a growing concern that procedural compliance may not have a direct impact on the protection of human subjects, our key point is that an ethical review system compliant with the national standards could serve as a strong framework to support and enhance the ethical quality of decision-making and judgement. We believe that being aware of how influential procedural compliance can be would help committees improve the ethical quality of their research review.